Research as Copaganda? An Abolitionist Framework for the Study of Police in Schools - Baggett, Hannah Carson; Andrzejewski, Carey E.; Richardson, LaKendrick; Porter, Brucie (Critical Education, 2026)
Recent global discourses about policing have interrogated the role of police (e.g., the #DefundthePolice movement) and amplified decades-old calls from scholars, educators, students, and activists to remove police from schools (e.g., #PoliceFreeSchools, #WeCameToLearn and nopoliceinschools.co.uk). Yet, copaganda continues to situate police, and police in schools, as necessary and desirable. In this essay, we present themes from the literature about school police. We then leverage those themes to advance a framework for the study of police in schools so that this research base does not function as copaganda. We emphasize an abolitionist approach to the study of police in schools that accounts for the history of policing as a racialized project, mobilizes critical and abolitionist perspectives, and takes seriously perspectives about defunding and removal in lieu of reform. We conclude by amplifying recommendations by abolitionist scholars and organizers.